Additional file 3 of “Mapping suicide prevention initiatives targeting Indigenous Sámi in Nordic countries” - Jon Petter A. Stoor (11659510); Heidi A. Eriksen (7778270); Anne C. Silviken (11659513) (2021)
Additional file 3: Supplementary Table 3. Problematizations, category and level of intervention suggested, yielded through applying the “What is the problem represented to be?”-approach on suicide prevention initiatives targeting Sámi in Norway, Sweden and Finland.